Peningkatan Literasi Keuangan di Kecamatan Pamulihan - Kurniawan, Iwan; Rahmawati, Ati (Setia Mengabdi: Jurnal Pengabdian kepada Masyarakat, 2024)
This community service initiative addresses the problem of low financial literacy in rural areas. The lack of socialization regarding financial literacy, primarily due to the community's educational level and needs, is a significant factor contributing to this issue. The purpose of this activity is to increase knowledge and prevent illegal loans in rural communities. The community service activity was carried out in Pamulihan Village, Pamulihan District, Sumedang Regency, in June 2024. The participants included 20 housewives and early childhood educators. The event consisted of an opening session, material introduction, games, and a closing session. As a result of these activities, the participants' knowledge of financial literacy improved, as evidenced by the evaluation of the game activities and initial efforts to increase awareness, which can be shared within the surrounding community.